GEOGRAPHIC AND SEX DIFFERENCES IN POSlTIONAL BEHAVIOR OF ORANG-UTANS - JITO SUGARDJITO SUGARDJITO; JOHN G. H. CANT (BRIN Publishing (Penerbit BRIN), 1994)
The basic aim of this paper is to present a synthesis of the field work that we have been conducting on the positional behavior of orang-utans. The data have been collected from two study sites, of which one was at Ketambe, Gunung Leuser National Park, northern Sumatra and the other at Mentoko, Kutai National Park, eastern Kalimantan. We attempt to interpret positional behavior in an ecological context, and we evaluate several hypotheses, some of which can not be tested conclusively at the present time.